Apresiasi Sastra Reseptif : Penerapan Pendekatan Emotif, Didaktis, dan Analitis terhadap Sastra Anak - Lidya Ananda; Rahma Ashari Hamzah; Hairuddin Hairuddin (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
This article discusses the application of emotive, didactic, and analytical approaches in receptive literary appreciation of children's literature. Receptive literary appreciation is the initial stage of appreciating literary works, emphasizing the reader's emotional engagement, evaluation, and acceptance of the content, particularly for children. The emotive approach focuses on the emotional and aesthetic elements of the work, the didactic approach highlights the understanding of ideas and moral values, while the analytical approach helps readers comprehend the structure and the author's message. Through the integration of these three approaches, children are expected to develop comprehensive cognitive, affective, and appreciative skills toward literature. The article also emphasizes the importance of appropriate teaching methods to enhance children's interest and understanding of literature, thereby supporting language development, imagination, and life values in children.